2005
DOI: 10.1080/03055690500095639
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model on improving maritime English training for maritime transportation safety

Abstract: Maritime services form an integral part of what regulatory agencies requires for the safe navigation and operation of vessels. Therefore, the maritime industry's compliance with governmental regulations and international protocols has been essential for maritime safety management. As a basis to this aspect, the preparation of maritime students as the forthcoming maritime officers in the future has been a crucial point by the maritime educators in terms of maritime safety. Although English was adopted as the of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Cole et al (2007), however, identified some disadvantages of this group of teachers: they did not have good English skills; they often challenged students excessively; their teaching contents were disorganized; and students could not follow them in class. The third group of ME teachers were native English speakers who were recommended by some ME researchers such as Yercan et al (2005). These native speakers were hired by many MET institutions in Korea (Davy and Noh 2010) and in Turkey (Fan et al 2015).…”
Section: Personnel Policymentioning
confidence: 99%
See 3 more Smart Citations
“…Cole et al (2007), however, identified some disadvantages of this group of teachers: they did not have good English skills; they often challenged students excessively; their teaching contents were disorganized; and students could not follow them in class. The third group of ME teachers were native English speakers who were recommended by some ME researchers such as Yercan et al (2005). These native speakers were hired by many MET institutions in Korea (Davy and Noh 2010) and in Turkey (Fan et al 2015).…”
Section: Personnel Policymentioning
confidence: 99%
“…Accordingly, Mercado et al (2013) proposed that the ME curriculum should take a holistic approach and cover both general English and ME because cadets who join offshore jobs instead of shipping jobs will need general English (Lu et al 2018). On the other hand, Yercan et al (2005) tried to develop a model curriculum for all MET but encountered two obstacles. The first obstacle was that all MET intuitions could not agree on a consensus from which to separate general English and ME and the level at which students should attend GE and ME.…”
Section: Curriculum Policymentioning
confidence: 99%
See 2 more Smart Citations
“…After the United States Department of Transportation (USDOT) and the United States Coast Guard (USCG) conducted examinations into the role of the human element in maritime disasters, amendments were made to the Seafarers' Training, Certification and Watch-Keeping (STCW) Convention in 1995 and 2010, stressing the benefits of using a common working language on board [9]. Evidence showed that over 80% of all maritime accidents were the result of human error.…”
Section: Maritime English As English For Specific Purposesmentioning
confidence: 99%